2003
DOI: 10.1556/avet.51.2003.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene cassettes of streptomycin-spectinomycin resistance of Hungarian Salmonella enterica serotype Typhimurium strains

Abstract: By PCR using the ant(3")-Ia primer pair the aadA gene was detected in 34 streptomycin-and spectinomycin-resistant Salmonella enterica serotype Typhimurium strains. Out of them 12 belonged to DT104 and 22 to non-DT104 phage type. Using different primer combinations it was demonstrated that this gene was integron-associated in all cases: in the DT104 strains it was generally contained by a 1 kb integron while in the majority of the non-DT104 strains by a 2.05 kb (less often by a 1.9 or 1 kb) integron. In the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…44 In recent years, the transfer of integrons harboring multiple drug-resistant gene cassettes or the joint transfer of two or more integrons into one isolate appears to be the basis for the rapid growth of MDR isolates. 45 Our conjugative plasmid pEHZJ1 possesses two class 1 integrons and an array of drug resistance genes, which may well pose a threat for the treatment of nosocomial infection. Previous reports showed that bla IMP-26 has high genetic similarity to bla IMP-4 , with only one position substitution at 145 (G-to-T change), 13 moreover, bla IMP-26 and bla IMP-4 were generally carried by a class 1 integron.…”
Section: Dovepressmentioning
confidence: 99%
“…44 In recent years, the transfer of integrons harboring multiple drug-resistant gene cassettes or the joint transfer of two or more integrons into one isolate appears to be the basis for the rapid growth of MDR isolates. 45 Our conjugative plasmid pEHZJ1 possesses two class 1 integrons and an array of drug resistance genes, which may well pose a threat for the treatment of nosocomial infection. Previous reports showed that bla IMP-26 has high genetic similarity to bla IMP-4 , with only one position substitution at 145 (G-to-T change), 13 moreover, bla IMP-26 and bla IMP-4 were generally carried by a class 1 integron.…”
Section: Dovepressmentioning
confidence: 99%
“…It was also described in other serovars (S. Agona and S. Newport), although with different resistance phenotypes (Boyd et al, 2002). DT104 S. Typhimurium strains were also found and characterised for their origin, for antibiotic resistance and for their integron content in Hungary (Szmollény et al, 2000;Pászti et al, 2001;Nógrády et al, 2003) but so far the occurrence of SGI1 has not been reported among Hungarian Salmonella strains. Therefore we identified and collected recent SGI1-positive Salmonella isolates and analysed their genetic relationships in relation to their origin.…”
mentioning
confidence: 92%
“…The appearance and spread of penta-resistant Salmonella Typhimurium definitive phage type 104 (DT 104) strains of human and animal origin in Hungary has been reported recently [6,7]. Preliminary data on the relationship of antibiotic resistance and integron carriage of S. Typhimurium strains have also been published on a collection of 105 strains isolated in 1998 [8,9]. However, there are no data at all on the antibiotic resistance and integron carriage of the other commonly isolated human Salmonella serotypes such as S. Enteritidis, S. Infantis, S. Hadar and S. Virchow from Hungary.…”
Section: Introductionmentioning
confidence: 99%